Adapting Technology Adoption Model to detect intention to use tiket.com’s online ticketing application - Lestari Ekatyas Eka; Siagian Dergibson (Business and Entrepreneurship Department, Kwik Kian Gie School of Business and Information Technology, Jakarta, 2021)
The Technologies Adoption Model is a popular tool for determining whether or not a person intends to accept new technology. However, this paradigm is only used in a few research for internet-based interactive technologies. The authors argue that, in addition to perceived simplicity of use and utility, the application content has a significant influence in increasing use intention for this technology. Trust, not attitude, should play a role in the mediation, as described in the original plan. To verify this conceptual framework, the authors use WrapPLS to analyze data from 155 respondents using structural equation modeling. According to the findings, the three antecedents have a favorable and significant direct effect on purchase intent. It's also confirmed that trust has an indirect influence. Aside from the system's utility, confidence, and convenience of use, the authors advise that ticket vendors present intriguing application content. Future research can look into the aspects that determine how well the system works.